How Synthesis Tasks Are Affected by Probability Format: A Making Numbers Meaningful Systematic Review - Natalie C. Benda; Mohit M. Sharma; Jessica S. Ancker; Michelle Demetres; Diana Delgado; Stephen B. Johnson; Brian J. Zikmund-Fisher (MDM Policy & Practice)
Background. To develop guidance on the effect of data presentation format on communication of health probabilities, the Making Numbers Meaningful project undertook a systematic review. Purpose. This article, one in a series, covers evidence about a “synthesis task,” in which readers examine stimuli to synthesize information about multiple features of health options, such as chances of both harm and benefit for a treatment. This article presents evidence of the effect of format on perceptual, cognitive, affective, and behavioral outcomes. Data Sources. MEDLINE, Embase, CINAHL, the Cochrane Library, PsycINFO, ERIC, ACM Digital Library; hand search of 4 journals. Finding Selection. Manual pairwise screening to identify experimental and quasi-experimental research comparing 2 or more formats for presenting quantitative health information to lay audiences. This article reports on 91 findings derived from 45 unique studies reported in 42 articles. Data Extraction. Pairwise extraction of information on stimulus (data in a data presentation format), cognitive task, and perceptual, affective, cognitive, or behavioral outcomes. Data Synthesis. Evidence was found about 6 outcomes: identification/recall, contrast, effectiveness perceptions/feelings, behavioral intentions/behavior, trust, and preference. No strong evidence was found. Moderate evidence suggests that for synthesis tasks, behavioral intention is not affected by whether the risk and benefit probabilities are in text or in tables, that people prefer tables to text for presenting this information, and that effectiveness feelings are not affected by whether or not numbers are supplemented by narratives. Limitations. Granular data extraction and evidence syntheses lead to narrow evidence statements. Conclusions. Current evidence on synthesis tasks is moderate strength at best. Future studies should enrich the evidence on how to present information needed to synthesize multiple features of health options, given the importance of this task. Highlights This study found a moderate number of studies assessing strategies for evaluating sets of probabilities conveying information such as risks and benefits. Evidence is moderate that although presenting sets of probabilities in table versus sentences may not affect behavioral intentions, people may prefer tables. Contrary to previous studies about probability feelings, moderate evidence suggested that narratives may not affect effectiveness feelings. Evidence was insufficient to draw conclusions regarding contrast, identification, and trust outcomes, and no studies assessed recall, categorization, computation, or discrimination outcomes.